New Trends in Translation and Interpretation Teaching/Training - AKPACA, SERVAIS MARTIAL (My University, 2020)
The aim of this paper is to discuss four aspects of translation and interpreting teaching, namely the pedagogical approach (i.e., objectivism vs. constructivism), translation ability and interpreter performance as well as translation and interpreting theory and practical classroom activities. The methodology is mostly descriptive and constructive in the sense that the paper “constructs” translation ability and interpreter performance and describes relevant teaching approaches to be adopted. One of the findings of the paper is that translation and interpreting teaching should either validate or change traditional pedagogical methods by new and more effective ones. Another finding of the paper is that translation and interpreting teaching should indicate clear-cut learning objectives, design adequate curricular materials and shed light on professional ethics and policies.
Keywords: pedagogical approach; translation ability; interpreter performance; theory; practice